Diel and vertical niche differentiation of frugivore communities feeding on Ficus nota (Blanco) Merr. - Cancio, Etienne Joaquim L. (Philippine Journal of Science, 2024)
Ficus species are keystone species in tropical ecosystems for frugivores. Nonetheless, ecological aspects of fig frugivory such as niche differentiation are understudied, leading to huge gaps in the knowledge of fig-frugivore interactions. We used camera traps to monitor the vertical and diel activity of frugivores feeding on a Ficus nota tree in Cavite, the Philippines for 70 d to determine vertebrate species feeding on Ficus nota and their niche differentiation mechanisms. We observed several mammalian taxa (pteropodid fruit bats, Rattus sp. and Paradoxurus philippinensis) and several avian taxa (Hypsipetes philippinus, Pycnonotus goiavier, Lanius cristatus, and Centropus viridis). All of the detected species were observed to be perching on, inspecting, or eating fruits. However, based on existing literature, two of the four bird species detected (L. cristatus and C. viridis) are known to be carnivorous. Diel niche differentiation was evident from the diurnal and nocturnal activity patterns of birds and mammals, respectively. We also detected temporal activity differences between pteropodids and P. philippinensis, hence suggesting temporal niche differentiation. Pteropodids were also more active in the terrestrial stratum, whereas non-pteropodids were more active in the arboreal stratum, hence suggesting vertical niche differentiation. Diel niche differentiation may be attributed to differences in food acquisition adaptations, whereas vertical niche differentiation may be attributed to differences in tree morphology between strata and in frugivore adaptations for mobility. These results show that Ficus nota acts as a food source and habitat for frugivores and non-frugivores and that interspecific interactions are mediated by niche differentiation. Our findings underscore the potential of Ficus nota as a species in restoration efforts to support seed-dispersing frugivores and other wildlife species, as well as the utility of camera trapping to survey frugivores in understudied habitats.